Andrew Ryan’s Ideology of Individualism in Bioshock: Rapture - Muhammad Hilfi Adanni (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
Ideology is a set of belief that determines how we act and think. Everyone in this world has an ideology that they hold tight unconsciously. Ideology in literature is planted in the characters of the story. In the Bioshock: Rapture, Andrew Ryan, the protagonist is depicted heavily to have an ideology of individualism. By using Louis Althusser‟s theory of ideology the writer will examine the ideology of Andrew Ryan. The result will be divided into three part, background of the character, the ideology of the character, and the factors that shape it. Keywords: Ideology, Individualism, Literature, Bioshock: Rapture